2017
DOI: 10.1016/j.compstruct.2017.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun nanofibers as reinforcement for composite laminates materials – A review

Abstract: In the last few decades nanofibers have been developed and introduced in a vast number of industrial and research applications. One of their most effective use is as interleaved reinforcement for composite laminate materials against delamination. Nanofibrous mats have the ideal morphology to be embedded between two plies of a laminate, and a vast and deep research has been carried out investigating their effect on the global behaviour of a composite laminate. This review is the first of its kind to date which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(122 citation statements)
references
References 110 publications
5
117
0
Order By: Relevance
“…According to these methods, the nano-interleaved samples have shown a 120-140% increase of G IC , compared to the virgin samples. The results are coherent with similar researches as reported in [27,28]. The fracture toughness is improved at both crack initiation and propagation for the fatigue tests as illustrated in Figure 4.…”
Section: Mechanical Resultssupporting
confidence: 92%
“…According to these methods, the nano-interleaved samples have shown a 120-140% increase of G IC , compared to the virgin samples. The results are coherent with similar researches as reported in [27,28]. The fracture toughness is improved at both crack initiation and propagation for the fatigue tests as illustrated in Figure 4.…”
Section: Mechanical Resultssupporting
confidence: 92%
“…Table summarizes the polymers used to produce nanofibers for composite laminates reinforcing purposes, by considering the structure in which they were interleaved in—unidirectional, plain weave or tow, and the main matrix reinforcement—carbon and glass fibers. It is clear that most of the nanofibers fabricated using electrospinning utilized thermoplastic polymers owing to the ability of these nanofibers to adhere more uniformly to the thermosetting resin resulting in a better bond to increase fracture toughness . Moreover, although they have various desired properties, thermosetting epoxies tend to be brittle because of a high degree of crosslinking.…”
Section: Recent Trends In Electrospinningmentioning
confidence: 99%
“…28 Reprinted with permission from Elsevier resulting in a better bond to increase fracture toughness. 15 Moreover, although they have various desired properties, thermosetting epoxies tend to be brittle because of a high degree of crosslinking. Therefore, it is commonly observed that hybrid or blends of nanofibers are being developed and deployed, which have multiple functionalities.…”
Section: Recent Trends In Electrospinningmentioning
confidence: 99%
See 1 more Smart Citation
“…Spraying of MWNT solutions has been used as a means of achieving well dispersed MWNT coatings [27]. Palazzetti [28] investigated laminates of 0/90 woven carbon fibre/epoxy resin prepregs with interleaves of electrospun nylon 6,6 nanofibres placed either symmetrically (two interleaves by the front and two interleaves by the back face of the laminate) or asymmetrically comprising three interleaves by the back face of the laminate. He found that the thickness of interleaves in the range of 25-50 µm did not affect the laminate performance, these interleaves brought improvements by up to 24% for Mode II fracture toughness, no difference in the impact curves, reduction of absorbed impact energy for impact energy values of 3 and 6 J and about a 13% increase in the absorbed impact energy for the impact energy value of 12 J for the asymmetric interleaf architecture (against an 8% increase in the absorbed impact energy for the symmetric interleaf architecture).…”
Section: Introductionmentioning
confidence: 99%